2014
DOI: 10.1007/s00404-014-3383-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of sublingual misoprostol with intracervical dinoprostone gel for cervical ripening in prelabour rupture of membranes after 34 weeks of gestation

Abstract: Sublingual misoprostol and intracervical dinoprostone at the dose studied are equally efficacious in achieving spontaneous vaginal delivery, reduction in induction-delivery interval and in reducing the need for oxytocin, in women after 34 weeks gestation with rupture of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(5 citation statements)
references
References 14 publications
4
1
0
Order By: Relevance
“…A research from India has also found significant difference in the post-induction mean Bishop's score when PGE1 was administered vaginally, and our finding is in concordance with this observation [7]. Significantly less proportion of patients required augmentation of labour with oxytocin or ARM (46.3 vs 62.1 %), and this correlates with evidence from Pakistan where oral PGE1 was compared with intracervical PGE2 [4] and by Niveditha et al [8] in PPROM. Our study has showed significant proportion of mothers had shorter induction-to-delivery time in PGE1 group than PGE2 group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A research from India has also found significant difference in the post-induction mean Bishop's score when PGE1 was administered vaginally, and our finding is in concordance with this observation [7]. Significantly less proportion of patients required augmentation of labour with oxytocin or ARM (46.3 vs 62.1 %), and this correlates with evidence from Pakistan where oral PGE1 was compared with intracervical PGE2 [4] and by Niveditha et al [8] in PPROM. Our study has showed significant proportion of mothers had shorter induction-to-delivery time in PGE1 group than PGE2 group.…”
Section: Discussionsupporting
confidence: 91%
“…Our study has showed significant proportion of mothers had shorter induction-to-delivery time in PGE1 group than PGE2 group. Similar observation has been found by Niveditha et al [8] when sublingual PGE1 was induced for PPROM after 34 weeks, and it has been shown to be more effective than intracervical PGE2. This finding is also in concordance with observation from Chaudhuri et al [9] when vaginal misoprostol was compared with PGE2.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients receiving sublingual administration of misoprostol have shorter induction to active phase, induction to delivery time intervals and also require less oxytocin for augmentation than the patients in which intra cervical dinoprostone gel was administered. Similar to present study, Wing et [8][9][10][11] . However Zhang et al did not find significant difference in Induction to delivery interval in two groups [12] .…”
Section: Discussionsupporting
confidence: 90%
“…Recently, intravaginal dinoprostone have greatly replaced the off-label usage of intravaginal misoprostol. Keeping in mind the possible side effects of misoprostol and the costly issues of dinoprostone it would be crucial to investigate the effectiveness of other agents within this field of obstetric practice (6) .…”
Section: Introductionmentioning
confidence: 99%